A 3D-printed adaptive cloaking–illusion-integrated metasurface. Issue 45 (11th November 2020) - Liang, Qingxuan; Li, Zhaohui; Jiang, Zijie; Duan, Yubing; Chen, Tianning; Li, Dichen
Abstract : An adaptive cloaking–illusion-integrated metasurface is realized for the first time by combining stereolithography of 3D printing technology and injection molding of liquid metals. Abstract : Metasurface, an artificial subwavelength-sized element possessing an excellent wavefront manipulation capability, has brought revolutionary progress in the design of cloaking and illusion devices. However, most existing metasurface-based cloaking or illusion devices can only exhibit a single electromagnetic function. A metasurface with integrated electromagnetic functionalities is highly in demand, but yet underexplored. Herein, a cloaking–illusion-integrated passive adaptive metasurface to polarization of the incident wave is successfully proposed in the microwave region. At different polarization, the metasurface can realize adaptive switching between cloaking and illusion functions. Both simulations and experiments demonstrate that the metasurface has good electromagnetic performance within a relatively broad bandwidth. This work provides a new strategy for the design and implementation of multiple cloaking and illusion functions integrated on the single passive metasurface and will facilitate real-life applications of the metasurface.